2017
DOI: 10.1080/09273972.2016.1276938
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Test Distance on Stereoacuity in Intermittent Exotropia

Abstract: Stereoacuity in X(T) was different according to test distance when measured controlling subtended angle of stereogram at both distances. Far stereoacuity was significantly worse than near stereoacuity when measured using test targets with both crossed and uncrossed disparities. Additionally, stereoacuity measured with crossed disparity was better than that with uncrossed disparity at both distances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Previous research has shown that these are consistent in the normal population, while others found they were quite different ( 28 , 29 ). The difference between distance and near stereopsis was significant when suffering from diseases ( 30 , 31 ). There is also little literature referring to stereopsis affected by meridional aniseikonia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that these are consistent in the normal population, while others found they were quite different ( 28 , 29 ). The difference between distance and near stereopsis was significant when suffering from diseases ( 30 , 31 ). There is also little literature referring to stereopsis affected by meridional aniseikonia.…”
Section: Introductionmentioning
confidence: 99%
“…It would be challenging to train all the nurses and pediatricians to perform a cover test for strabismus detection and so screening protocols opt for the simpler stereo testing (typically Randot), which can miss cases of intermittent strabismus. Direct evaluation of strabismus (rather than relying on a stereopsis test) is particularly important in intermittent strabismus, where stereopsis can be normal or near normal causing most cases to be missed [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Direct evaluation of strabismus (rather than relying on a stereopsis test) is particularly important in intermittent strabismus, where stereopsis can be normal or near normal causing most cases to be missed. 5,6 In 2002, the American Academy of Pediatrics strongly endorsed the development of cost-effective imagebased screening (photoscreening) as a means to extend screening to all children. 7 The red re ex (Bruckner) 8 and the corneal re ex (Hirschberg) techniques are the two most common strabismus photoscreening methods.…”
Section: Introductionmentioning
confidence: 99%